2019
DOI: 10.1177/1528083718823292
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effect of reinforcement parameters on the mechanical properties of natural fibre-woven composites by Taguchi method

Abstract: Process optimization is the key task of any engineering application to maximize the desirable output by optimizing the range of process parameters. In this research work, jute composites were fabricated by the hand lay-up method with the aim of optimizing the process parameter such as yarn linear density, fabric areal density and fabric laying angle on the mechanical properties of the textile composite structures using the Taguchi L9 orthogonal matrix. The plain-woven and twill-woven fabrics of Jute fabrics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The S/N ratio increases as the fiber content increases. 24 When the S/N ratios of the tensile, 3-point bending, and drop weight experiments are examined (Figure 7), it is seen that the mechanical properties increase as the fiber content increases. However, it was observed that the effect decreased as the fiber content increased.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S/N ratio increases as the fiber content increases. 24 When the S/N ratios of the tensile, 3-point bending, and drop weight experiments are examined (Figure 7), it is seen that the mechanical properties increase as the fiber content increases. However, it was observed that the effect decreased as the fiber content increased.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…According to this approach, the following equation (2) is used to calculate the S/N ratio. 24 where y is the measurement value and n is the number of experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study is to reach the highest value. The equation below is used to calculate the S/N ratio according to this method [26]. S/N ratios of test results are shown in Table 4.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…17 Over the last few decades, the use of natural products for pharmacological purposes has increased over the world. 18 Flax fibers, as an example of biologic material, have been considered due to their intrinsic mechanical properties and biocompatible with the human tissues. 19 Flax fibres have been considered the important biomaterials, including sutures.…”
Section: Introductionmentioning
confidence: 99%